PEMBERDAYAAN LOCAL WISDOM DALAM PENYELESAIAN KONFLIK DI KERATON SURAKARTA HADININGRAT - , Sutapa Mulja Widada, Istadiyantha (PARENTAL, 2015)
AbstractThe purpose of this study was to describe the root causes of conflict and the palace of King Twins conflict resolution patterns Keraton Surakarta Sultanate . The method used is descriptive method sosiolegal . This study is located in the Keraton Surakarta using primary data and secondary data. Techniques of qualitative data analysis by using the theoretical interpretation. The results showed that the root of the problem is basically this conflict began Keraton Surakarta since the death of Paku Buwana XII on June 11, 2004. The conflict between the heir to the throne of Kanjeng Gusti Pangeran Harya (KGPH) Hangabehi and KGPH Tedjowulan born of different mothers. Patterns of conflict resolution involving a third party (mediation) mechanisms beyond traditional law paugeran palace. Lastly, Mediation of legal protection based Surakarta Mayor Letter No. 181.1/6619/SJ Minister mentioned that the mayor coordinate with Deliberation forums Regional Head (Muspida) and family Keraton Solo Kasunanan, to resolve conflicts and protect the palace as a cultural heritage.Keywords: Mediation, Conflict, and Local Wisdom